2018
DOI: 10.3390/genes9010048
|View full text |Cite
|
Sign up to set email alerts
|

PGC1α: Friend or Foe in Cancer?

Abstract: The PGC1 family (Peroxisome proliferator-activated receptor γ (PPARγ) coactivators) of transcriptional coactivators are considered master regulators of mitochondrial biogenesis and function. The PGC1α isoform is expressed especially in metabolically active tissues, such as the liver, kidneys and brain, and responds to energy-demanding situations. Given the altered and highly adaptable metabolism of tumor cells, it is of interest to investigate PGC1α in cancer. Both high and low levels of PGC1α expression have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 125 publications
(243 reference statements)
2
59
0
1
Order By: Relevance
“…Moreover, the activity of PGC1α-ERRα negatively correlated with levels of oncogenic transcription factor MYC [98]. However, it has to be added that the effect of PGC1α differs across various tumors (for review, see [99]). A metabolomics analysis of triple-negative breast cancer cells with an elevated level of MYC demonstrated a four-fold increase in production of palmitoylcarnitine when compared to control mammary gland.…”
Section: Slc22a5 and Fatty Acid Oxidation In Cancermentioning
confidence: 99%
“…Moreover, the activity of PGC1α-ERRα negatively correlated with levels of oncogenic transcription factor MYC [98]. However, it has to be added that the effect of PGC1α differs across various tumors (for review, see [99]). A metabolomics analysis of triple-negative breast cancer cells with an elevated level of MYC demonstrated a four-fold increase in production of palmitoylcarnitine when compared to control mammary gland.…”
Section: Slc22a5 and Fatty Acid Oxidation In Cancermentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor-γ coactivator (PGC)-1α is a transcriptional coactivator that was initially identified in an interaction with nuclear receptor peroxisome proliferator-activated receptors (PPARγ) in response to lower temperatures [1]. In addition to its role in adaptive thermogenesis, PGC-1α is presently described as a master regulator of mitochondrial biogenesis and function, including oxidative phosphorylation (OXPHOS) and reactive oxygen species (ROS) detoxification [2]. In recent years, PGC-1α has been associated with many inflammatory and meta-bolic diseases, and its crucial role regulating mitochondrial function, oxidative stress, and metabolic pathways in diverse tissues has been revealed [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The role of PGC1α in carcinogenesis has not been clear. Most experts believe early in carcinogenesis, PGC1α may be downregulated, while in the later stages of tumour progression, PGC1α is often upregulated [44]. A study in mice showed that PGC1α regulates mitochondrial function and promotes tumour growth [45].…”
Section: Discussionmentioning
confidence: 99%